PENDIDIKAN SASTERA DALAM KONTEKS KERAGAMAN BUDAYA: PRINSIP DAN PENDEKATAN KE ARAH KEJAYAAN - Md. Salleh Yaapar (Dialektika: Jurnal Bahasa, Sastra, dan Pendidikan Bahasa dan Sastra Indonesia, 2014)
Cultural diversity in human life in the country context or in the world context is an essence. This case was duly understood and commonly accepted, but what is true is not always like that.On the other hand, there is often tension or conflict in the world and in the regional caused by cultural diversity. This paper shows the brooding of literature and reasonable principles espoused to ensure social harmony, coexistence and peace in the midst of diversity and cultural differences. First, the importance of being open to differences and accept it although not compatible with their own beliefs and practices (toleration) in order to achieve common goals. Second, the need to honor or celebrate differences (celebration) in order to achieve social cohesion, peace and perfect unity. To achieve the objectives of the above principles, should be practiced the current method and approach.In the context of language and literary education in a country like Indonesia or Malaysia, the spirit of cultural diversity can be developed through a number of ways. Among them, by utilizing the discipline of Comparative Literature which clearly stipulates that are cross-cultural studies. Next, using a curriculum that focuses on literary works such as Jalan Menikung and Hikayat Hang Tuah which is featuring side of cultural diversity, especially around the theme of harmony between human beings.